Sporothrix schenckii lipid inhibits macrophage phagocytosis: Involvement of nitric oxide and tumour necrosis factor-alpha - Carlos, Iracilda Zeppone [UNESP]; Sgarbi, DBG; Santos, G. C.; Placeres, MCP (Blackwell Publishing, 2003)
The role of cell-wall compounds in the immune response to sporotrichosis is unknown. The effect of cell-wall compounds and exoantigen obtained from Sporothrix schenckii in macrophage/fungus interaction was analysed with respect to nitric oxide (NO) and tumour necrosis factor-alpha (TNF-alpha). The lipid compound of the cell wall plays an important role in the pathogenesis of this mycosis and was found to inhibit the phagocytic process and to induce high liberation of NO and TNF-alpha in macrophage cultures in the present study. This is a very interesting result because it is the first report about one compound of the fungus S. schenckii that presents this activity.